2021
DOI: 10.1029/2021gl092376
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Interaction of Cold and Hot Protons With an Oblique EMIC Wave Near the Dayside Reconnecting Magnetopause

Abstract: Electromagnetic ion cyclotron (EMIC) waves are generated in various regions of the Earth's magnetosphere when hot (keV to tens of keV) ions have T ⊥ > T ‖ (e.g.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 50 publications
4
15
0
Order By: Relevance
“…Kim and Johnson, (2016) also demonstrated that larger normal angle waves can propagate toward smaller L-shell although they calculated the raypath up to L ∼6 (Figure 4 in Kim & Johnson, 2016). Recently, Toledo-Redondo et al (2021) showed EMIC wave can also be generated at oblique angles when source region consists of a small amount of heavy ions and a large amount of cold protons.…”
Section: Discussionmentioning
confidence: 98%
“…Kim and Johnson, (2016) also demonstrated that larger normal angle waves can propagate toward smaller L-shell although they calculated the raypath up to L ∼6 (Figure 4 in Kim & Johnson, 2016). Recently, Toledo-Redondo et al (2021) showed EMIC wave can also be generated at oblique angles when source region consists of a small amount of heavy ions and a large amount of cold protons.…”
Section: Discussionmentioning
confidence: 98%
“…It is worth noting that these points are generally different from those of maximum instability. Another situation occurs when the instability, for example, due to wave-particle heating, creates a second particle group that differs from the already existing one due to different temperature or speed, for example, Teng et al (2019), Usanova (2021), andToledo-Redondo et al (2021). In this case, oscillitons can arise in which groups of particles with the same mass participate, but which differ from each other in other parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Especially valuable for confirming the oscilliton concept is the evaluation of multi-point measurements by Toledo-Redondo et al (2021). According to their interpretation, the observed EMIC waves in the H + band (ω/ Ω p ∼ 0.7) arise from the momentum exchange of two groups of cold and warm protons via the mediating electromagnetic field.…”
Section: Discussionmentioning
confidence: 99%